Preservative-free therapy for glaucoma after corneal refractive surgery - A.A. Antonov; I.V. Kozlova; T.S. Mitichkina; I.I. Vedmedenko (РМЖ "Клиническая офтальмология")
А.А. Antonov1, I.V. Kozlova1, T.S. Mitichkina1, I.I. Vedmedenko2 1Scientific Research Insitute of Eye Diseases, Moscow, Russian Federation 2Sechenov University, Moscow, Russian Federation Corneal refractive surgery is now a common technique to improve the quality of life. In addition to classical issues and difficulties, this results in the reduced quality of glaucoma screening and monitoring in a complex group with myopic refraction at baseline. In patients who underwent corneal refractive surgery corneal shape depends on the intraocular pressure (IOP) greater than in patients with intact fibrous tunic. Moreover, its biomechanic properties are more diverse. As a result of an increased percentage of these patients and their aging, glaucoma is diagnosed more often in this group. In these patients, glaucoma is a specific condition because of low significance of classical screening and diagnostic tools. IOP-lowering treatment should not affect ocular surface but provide a stable IOP level. Diagnostic and treatment modalities for refractive disorders are promising for broad clinical application. Preservative-free prostaglandin analogue, tafluprost, is a novel IOP-l owering therapeutic agent to prescribe after corneal refractive surgery. Keywords: glaucoma, refractive surgery, radial keratotomy, intraocular pressure, tonometry, progressive hyperopia, preservative-free therapy, timolol. For citation: Antonov А.А., Kozlova I.V., Mitichkina T.S., Vedmedenko I.I. Preservative-free therapy for glaucoma after corneal refractive surgery. Russian Journal of Clinical Ophthalmology. 2019;19(3):165–169. About the authors: 1Alexey A. Antonov — MD, PhD, Leading Researcher of Glaucoma Department, ORCHID iD 0000-0002-5171-8261; 1Irina V. Kozlova — MD, PhD, Leading Researcher of Glaucoma Department, ORCHID iD 0000-0003-3885-9649; 1Tatiana S. Mitichkina — MD, PhD, Senior Researcher of Department of Refractive Disorders, ORCHID iD 0000-0002-8124-4001; 2Irina I. Vedmedenko — MD, PhD, Assistant of the Department of Eye Diseases, ORCHID iD 0000-0002-1104-9315. 1Scientific Reseach Institute of Eye Diseases. 11A, Rossolimo str., Moscow, 119021, Russian Federation. 2Sechenov University. 8/2, Trubetskaya str., Moscow, 119991, Russian Federation. Contact information: Alexey A. Antonov, e-mail: niigb.antonov@gmail.com. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 21.02.2019.